2020
DOI: 10.1093/rheumatology/keaa504
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo syndrome and rheumatic diseases—a critical systematic review

Abstract: Since its description in 1990, Takotsubo syndrome (TTS), an acute cardiac condition triggered by physical or emotional stress, has been believed to be related to catecholamine surge from overwhelming sympathetic activity. While symptomatology, biochemical features, ECG and echocardiogram alterations are largely indistinguishable from acute coronary syndrome, the absence of culprit coronary lesions often necessitates further investigations, uncovering underlying inflammatory processes. Mechanistically, animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Other factors involved in the pathophysiology of TTS include estrogen deprivation, inflammation and immune activation ( 3 ). In line with the latter hypothesis, there is a potential link between rheumatological disorders and TTS ( 11 ). A retrospective epidemiologic study showed that the prevalence of TA among all TTS-related hospitalizations was 0.05%.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Other factors involved in the pathophysiology of TTS include estrogen deprivation, inflammation and immune activation ( 3 ). In line with the latter hypothesis, there is a potential link between rheumatological disorders and TTS ( 11 ). A retrospective epidemiologic study showed that the prevalence of TA among all TTS-related hospitalizations was 0.05%.…”
Section: Discussionmentioning
confidence: 75%
“…During admission, patients with TA and TTS had a higher rate of stroke, respiratory failure, necessity of mechanical ventilation and higher healthcare resource utilization, highlighting the possible role of TA in the prognosis of TTS ( 12 ). However, given the paucity of reports linking TA and other autoimmune diseases with TTS even though both diseases have a predilection for middle-aged women, it has been suggested that immunosuppressive treatment of these rheumatological disorders might protect against pro-inflammatory responses to catecholamine surge seen in TTS ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autopsy studies have reported inflammatory, fibrotic as well as vascular myocardial abnormalities in 80% of SSc patients. 3 The diagnosis of primary cardiac disease, however, remains challenging as clinical findings of cardiac abnormalities in the early stage of disease are uncommon and, if present, very subtle and non-specific. 2 The diagnostic workup is further hampered due to the lack of criteria for distinguishing between primary cardiac involvement and other more common causes of cardiomyopathy such as hypertension and ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, recent investigation proposed an additional inflammatory pathway which might be relevant in the context of autoimmune rheumatic diseases. 3,4 Although TTS has traditionally been regarded as a benign, transient condition, it has recently been reported that acute mortality may be significant and patients can experience persistent symptoms, even though left ventricular function is completely normalized. 5 In addition, approximately 1% to 4% of patients will experience a recurrent episode of TTS, most commonly within 5 years after the first event.…”
Section: Introductionmentioning
confidence: 99%